PENGARUH INVESTASI DAN HUMAN CAPITAL TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2011-2020 - Uma Kusumawati Mutmainah; Disman Disman; Susanti Kurniawati (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2021)
The background of the study is problems during the Covid-19 pandemic that hit Indonesia, the government implemented a policy of limiting social activities to the community which had an impact on national economic activity, resulting in a decline in economic growth. According to the New Growth economic theory, investment in physical capital and human capital is the main key to increasing economic productivity. This study aims to determine the effect of domestic investment, foreign investment and human capital on economic growth in Indonesia. The method used in this study is a quantitative method and obtains secondary data with documentation techniques from the Central Statistics Agency which combines time series data from 2011 to 2020 and cross-sectional data in 34 provinces in Indonesia. Testing the data in this study using panel data test with Fixed Effect model. The results of the study show that: (i) Domestic Investment Realization has a positive and insignificant effect on economic growth; (ii) Realized foreign investment has a positive and significant effect on economic growth; (iii) Human Capital has a negative and significant effect on growth economy; (iv) PMDN, PMA and Human Capital together have a positive effect on economic growth in Indonesia.